Intellectual capital efficiency and its contribution to financial stability in Islamic banks: a study of the gulf countries - Ur Rehman, Aziz; Sharofiddin, Ashurov; Khan Orakzai, Abdul Salam (Karachi Hamdard Foundation Pakistan, 2025)
The stability of Islamic banks is critical to the financial systems of the Gulf Cooperation Council (GCC) countries, yet the role of intellectual capital in supporting that stability remains underexplored. This study addresses the research problem of insufficient understanding of how Intellectual Capital Efficiency (ICE) specifically Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Relational Capital Efficiency (RCE)—affects the financial stability of Islamic banks. The primary objective is to empirically investigate the contribution of ICE components to enhancing financial stability, using reliable performance metrics such as the capital-to-asset ratio and net profit margin. To achieve this, the study employs a dynamic panel data approach using the hierarchical Generalised Method of Moments (GMM) estimator. This methodology is justified due to its effectiveness in handling endogeneity issues, unobserved heterogeneity, and autocorrelation in panel data. The dataset includes 37 Islamic banks operating across six GCC countries including Saudi Arabia, Kuwait, Oman, Qatar, Bahrain and United Arab Emirates from 2010 to 2021. ICE variables are introduced sequentially into the model to measure their individual and combined effects. The results reveal that HCE and SCE have a statistically significant positive impact on financial stability, while the influence of RCE is more context dependent. These findings validate the resource-based theory and provide practical insights for bank managers and policymakers, encouraging strategic investments in intellectual capital to sustain institutional resilience in competitive Islamic financial markets